CTHRC1: An Emerging Hallmark of Pathogenic Fibroblasts in Lung Fibrosis - Zhussipbek Mukhatayev; Altynay Adilbayeva; Jeannette Kunz (Cells, 2024)
Pulmonary fibrosis is a chronic, progressive, irreversible lung disease characterized by fibrotic scarring in the lung parenchyma. This condition involves the excessive accumulation of extracellular matrix (ECM) due to the aberrant activation of myofibroblasts in the alveolar environment. Transforming growth factor beta (TGF-β) signaling is a crucial driver of fibrogenesis because it promotes excessive ECM deposition, thereby leading to scar formation and lung damage. A primary target of TGF-β signaling in fibrosis is Collagen Triple Helix Repeat Containing 1 (CTHRC1), a secreted glycoprotein that plays a pivotal role in ECM deposition and wound repair. TGF-β transcriptionally regulates CTHRC1 in response to tissue injury and controls the wound healing response through functional activity. CTHRC1 may also play an essential role in re-establishing and maintaining tissue homeostasis after wound closure by modulating both the TGF-β and canonical Wnt signaling pathways. This dual function suggests that CTHRC1 regulates tissue remodeling and homeostasis. However, deregulated CTHRC1 expression in pathogenic fibroblasts has recently emerged as a hallmark of fibrosis in multiple organs and tissues. This review highlights recent studies suggesting that CTHRC1 can serve as a diagnostic and prognostic biomarker for fibrosis in idiopathic pulmonary fibrosis, systemic sclerosis, and post-COVID-19 lung fibrosis. Notably, CTHRC1 expression is responsive to antifibrotic drugs that target the TGF-β pathway, such as pirfenidone and bexotegrast, indicating its potential as a biomarker of treatment success. These findings suggest that CTHRC1 may present new opportunities for diagnosing and treating patients with lung fibrosis.